Analisis Kualitas Layanan Website SMA Terhadap Kepuasan Siswa Menggunakan Metode Webqual 4.0 - Jefri, Antonius; Purnama, Benni; Mulyono, Herry (TIN: Terapan Informatika Nusantara, 2024)
The problem with the Xaverius 1 City High School website in Jambi is that there are several shortcomings, namely information that is not updated, the web often experiences bugs or errors when accessing available features, loading takes too long, the web appearance is too old-fashioned and does not have clear instructions. The purpose of this study was to analyze the service quality of the Xaverius 1 High School website in Jambi City by applying the webqual 4.0 method and to determine the effect of research variables on website user satisfaction. research that has been carried out using the webqual 4.0 method where there are 3 independent variables (quality of use, quality of information, quality of interaction) and one dependent variable (user satisfaction) and in this study adopted one additional variable from the EUCS method, namely content. This study is a multiple linear regression which produces two hypotheses accepted while 3 hypotheses are rejected. The rejected hypotheses include H1 (quality of use), H2 (quality of information) and H3 (quality of interaction) on user satisfaction, while the accepted hypothesis is H4 (content) there is a relationship with user satisfaction, and H5 regarding all variables influencing user satisfaction. In this study, the researchers suggested to SMA Xaverius 1 Jambi City to improve the website in terms of usability quality, information quality and interaction quality on the website. Which can be seen in the research results of the three qualities have no effect on user satisfaction.